2021
DOI: 10.1111/tbed.14319
|View full text |Cite
|
Sign up to set email alerts
|

Diversity ofAnaplasmaspecies and importance of mixed infections in roe deer from Spain

Abstract: Although wildlife can act as reservoirs of some Anaplasma species, studies on the presence and distribution of Anaplasma spp. in wild cervids are mainly limited and focused on zoonotic species. In order to identify the Anaplasma species in roe deer from Spain and to detect co-infections, 224 spleen samples were tested for Anaplasma spp. using a commercial qPCR; positive samples were further characterized using generic 16S rRNA primers and species-specific primers targeting the msp2 and groEL genes.Anaplasma DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
(139 reference statements)
1
7
0
Order By: Relevance
“…mongolitimonae are the etiological agents of the MSF‐like (Oteo & Portillo, 2012). Anaplasma phagocytophilum was not detected in the studied tick population agreeing with previous studies reporting a low prevalence in I. ricinus (0.4%) in woodland areas from the same region (Remesar, Prieto, et al, 2021). Regarding the novel Rickettsia spp., further studies are needed for completing their characterization and for evaluating their pathogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…mongolitimonae are the etiological agents of the MSF‐like (Oteo & Portillo, 2012). Anaplasma phagocytophilum was not detected in the studied tick population agreeing with previous studies reporting a low prevalence in I. ricinus (0.4%) in woodland areas from the same region (Remesar, Prieto, et al, 2021). Regarding the novel Rickettsia spp., further studies are needed for completing their characterization and for evaluating their pathogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…The following supporting information can be downloaded at: , Table S1. Primers for the amplification of sequences of ticks and tick-borne pathogens [ 13 , 33 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]; Supplementary Data. The electrophoretic detection of amplification of tick-borne pathogens PCR products on agarose gel.…”
mentioning
confidence: 99%
“…Anaplasma capra was first confirmed to be a human pathogen in 2015 ( Li et al, 2015 ) and has been mainly identified in livestock based on sequences deposited in GenBank and previous studies ( Guo et al, 2018 ; Amer et al, 2019 ; He et al, 2021 ; Remesar et al, 2022 ; Sahin et al, 2022 ). In this study, only one partial 16S rRNA sequence was obtained, and we conjectured that this may have resulted from a low bacterial load or DNA degradation by some enzymes in the host.…”
Section: Discussionmentioning
confidence: 99%